Monoamine Levels and Parkinson’s Disease Progression: Evidence From a High-Performance Liquid Chromatography Study - Wichit, Patsorn; Thanprasertsuk, Sekh; Phokaewvarangkul, Onanong; Bhidayasiri, Roongroj; Bongsebandhu-phubhakdi, Saknan (Frontiers in neuroscience, 2021)
Parkinson’s disease (PD) is associated with dysfunction of monoamine neurotransmitter systems. We investigated changes in the levels of monoamine and their metabolites in PD patients, together with their association to clinical profiles. PD patients and age-matched control subjects ( n = 40 per group) were enrolled. Using high-performance liquid chromatography (HPLC) with an electrochemical detector, levels of monoamines (dopamine, DA; norepinephrine, NE; epinephrine, EPI; and serotonin, 5-HT) were measured in plasma, while the metabolites (homovanillic acid, HVA; vanillylmandelic acid, VMA; and 5-hydroxyindoleacetic acid, 5-HIAA) were measured in urine. Plasma DA level was not significantly different between PD and control groups. PD patients had significantly higher plasma NE but lower EPI and 5-HT levels. PD patients had a significantly higher HVA/DA ratio and lower VMA/NE ratio than control subjects, while the 5-HIAA/5-HT ratio was not different between the groups. Regarding the association between monoamine levels and clinical profiles, the DA level had a negative relationship with disease duration and the 5-HT level had a negative relationship with severity of motor impairment. These findings emphasized the involvements of several neurotransmission systems and their association with clinical profiles in PD patients, demonstrated by quantification of monoamine levels in peripheral body fluids. This could benefit appropriate pharmacological treatment planning in respect of monoamine changes and might also help predict subsequent clinical symptoms.